2013
DOI: 10.1073/pnas.1221609110
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor affinity and avidity defines antitumor response and autoimmunity in T-cell immunotherapy

Abstract: T cells expressing antigen-specific T-cell receptors (TCRs) can mediate effective tumor regression, but they often also are accompanied by autoimmune responses. To determine the TCR affinity threshold defining the optimal balance between effective antitumor activity and autoimmunity in vivo , we used a unique self-antigen system comprising seven human melanoma gp100(209–217)-specific TCRs spanning physiological affinities (1–100 μM). We found that in vitro and in vivo T-cell responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
215
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 61 publications
14
215
2
1
Order By: Relevance
“…Although it seems counterintuitive, this is likely due to the reduced ability of high-affinity CTL to undergo serial triggering, where one MHC-peptide complex sequentially engages several TCR to achieve a critical activation threshold (23)(24)(25). Indeed, our data support findings from both mouse (26) and human (27) antimelanoma CTL where CTL with higher-avidity TCR do not elicit more potent antitumor activity than those with loweravidity TCR. An advantage of using CTL expressing low-affinity TCR is that the risk for toxic recognition of low-abundance TAA in normal tissues may be averted.…”
Section: Discussionsupporting
confidence: 60%
“…Although it seems counterintuitive, this is likely due to the reduced ability of high-affinity CTL to undergo serial triggering, where one MHC-peptide complex sequentially engages several TCR to achieve a critical activation threshold (23)(24)(25). Indeed, our data support findings from both mouse (26) and human (27) antimelanoma CTL where CTL with higher-avidity TCR do not elicit more potent antitumor activity than those with loweravidity TCR. An advantage of using CTL expressing low-affinity TCR is that the risk for toxic recognition of low-abundance TAA in normal tissues may be averted.…”
Section: Discussionsupporting
confidence: 60%
“…The TCR must be chosen to target tumor-specific antigens, such as cancer-testis antigens or neoantigens, because infusions of T cells with transgenic TCRs that recognize antigens shared by normal tissue induce an unacceptable degree of toxicity 92 . Experiments with a panel of TCRs with varied affinity and targeting self-antigens show that the induction of anti-tumor activity and autoimmunity are closely coupled 93 . Furthermore, autoimmune syndromes might occur following the adoptive transfer of transgenic T cells that retain the endogenous TCR 94 , presumably owing to the formation of heterodimers that create self-reactive specificities.…”
Section: Box 1 Adoptive T Cell Therapymentioning
confidence: 99%
“…34 In agreement with these studies, in our study we observed that the 29 gp100 209-217 (210M)-specific clones sequenced from three patients were associated with a restricted TCR repertoire, irrespective of the treatment received (Figure 1░C). Of relevance, differently from available literature on gp100 + T-cell clones, showing only TCRBV region families, 35-37 we extended our TCR analysis on CDR3 Vβ sequences, as a more accurate measure of TCR diversity. A detailed search in different public databases specific for TCR indicated that no gp100 209-217 TCR clonotype was recorded.…”
Section: Discussionmentioning
confidence: 99%